Effectiveness of Cold Compress in Preventing Hematoma in Post Percutaneous Coronary Intervention (PCI) Patients: A Systematic Literature Review - Ifana Yunike Pristya; Elly Nurachmah; Riri Maria (GLOBAL HEALTH SCIENCE GROUP, 2025)
Percutaneous Coronary Intervention (PCI) is currently indicated for patients experiencing acute coronary syndrome and individuals with chronic stable angina that is refractory to optimal medical therapy. Advancements in devices, stent design, adjunctive technology, and the development of more potent and effective antiplatelet therapies have contributed to improved outcomes. However, major periprocedural complications during PCI remain a concern, with an overall transulnar access site complication rate of 41%, a vasospasm incidence of 7%, and a hematoma occurrence of 29%. Cold compress application is widely used due to its physiological effects, including vasoconstriction, reduced tissue metabolism, increased blood viscosity, and local anesthetic properties. Cold compresses can decrease blood flow and capillary permeability by inducing arteriolar vasoconstriction, thereby reducing bleeding.Objective: This study aims to examine the implementation of cold compress therapy in preventing hematoma in post-Percutaneous Coronary Intervention (PCI) patients.Methods: This study employs a systematic literature review approach. Data synthesis was conducted by analyzing eight studies that met quality assessment standards and inclusion-exclusion criteria. The databases used for literature retrieval included Google Scholar, PubMed, ScienceDirect, EBSCO, and ProQuest. The findings were processed and presented in tabular form.Result: Cold compresses can help reduce hematoma and pain after a Percutaneous coronary Intervention (PCI), cold compresses can also help prevent hematomas. How cold compresses help cold compresses vasoconstrict blood vessels and cold compresses speed up blood clotting.Conclusion: The reviewed articles indicate that the application of an ice pack or cold compress is more effective in reducing pain and preventing hematoma caused by catheter removal in patients undergoing Percutaneous Coronary Intervention (PCI).